Pembelajaran Bahasa dan Sastra Indonesia terhadap Pemanfaatan Koleksi Perpustakaan oleh Siswa kelas IX SMP Unismuh Makassar - Maria Ulviani; Siti Suwada Rimang; B Syukroni Baso (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: Learning Indonesian Language and Literature towards the Use of Library Collections by Students of Grade IX students of the First Menegah Schoolof Unismuh Makassar. This research aimsto determine the influence of learning Indonesian language and literature on the use of library collections at SMP Unismuh Makassar. This research uses quantitative methods. The data collection techniquein this study uses a questionnaire that is circulated toall class XI students. Population using Simple Random Sampling Technique. Basedon the results of the study, it shows that the learning of indonesian language and literatureis classified as good or high level. The results were obtained from 59.77% of respondents utilizing library collections for Indonesian language and literature subjects twice a week. Meanwhile, the utilization of library by Grade IX students of the First Menegah Schoolof Unismuh Makassar is classified as a good level. Based on the results that the author can conclude 4.27% that respondents use library collections as a source of information to increase knowledge so that students gain insight and obtain materials or materials to add knowledge.